SUPPRESSION OF INCIDENCE OF RHIZOCTONIA SOLANI IN RICE BY SIDEROPHORE PRODUCING RHIZOBACTERIAL STRAINS BASED ON COMPETITION FOR IRON - Naureen, Zakira; Hafeez, Fauzia Y.; Hussain, Javid; Al Harrasi, Ahmed; Bouqellah, Nahla; Roberts, Michael R. (European Scientific Journal, ESJ, 2015)
Rice is a major crop in much of the developing world, where disease management using agrochemicals is not economically practical, nor environmentally safe. The identification of biocontrol agents therefore presents a useful alternative. Here, we screened bacterial strains isolated from the rhizosphere of rice plants, and identified a number of these that exhibit antagonistic activity towards the fungal pathogen, Rhizoctonia solani, the causative agent of rice sheath blight disease. Correlation analysis with different metabolites produced by these bacteria revealed that antagonism was strongly correlated with the quantity of siderophores produced by individual strains, and was increased under iron-limiting conditions. Selected high-siderophore-producing strains were found to promote the growth of rice plants, possibly via the solubilisation of soil phosphates, nitrogen fixation and the production of phytohormones. These same PGPR also conferred resistance against sheath blight disease, which resulted in significant yield increases in infected plants. A consortium of the selected strains was especially effective in both growth promotion and disease suppression, and generally performed better than treatment with the fungicide, benlate. Molecular analysis indicated that the PGPR strains tested enhance plant defence gene expression, and may therefore activate induced systemic resistance in rice. Our work has identified a series of rhizobacterial strains able to promote plant growth and provide effective resistance against sheath blight disease in rice and which therefore have potential for application as biocontrol agents in agriculture.